2018
DOI: 10.1515/iss-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography donor liver volumetry before liver transplantation in infants ≤10 kg: does the estimated graft diameter affect the outcome?

Abstract: Aim of the studyLiving donor liver transplantation (LDLT) is regularly performed in small-sized infants. Computed tomography (CT)-based donor liver volumetry is used to estimate the graft size. The aim of our study was to assess the results of CT liver volumetry and their impact on the clinical outcome after LDLT in extremely small-sized infants.Patients and methodsIn this study, we included all patients with a body weight of ≤10 kg who underwent living related liver transplantation at our centre between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, despite the difference in volume and weight, the discrepancy between estimated and actual graft weights remained almost consistent across genders, in support of Schukfeh and colleagues' ndings. Although their research indicated that while male donor grafts were considerably thicker (p < 0.005), the estimated graft weight between male and female donors showed no signi cant difference [17].…”
Section: Discussionmentioning
confidence: 92%
“…However, despite the difference in volume and weight, the discrepancy between estimated and actual graft weights remained almost consistent across genders, in support of Schukfeh and colleagues' ndings. Although their research indicated that while male donor grafts were considerably thicker (p < 0.005), the estimated graft weight between male and female donors showed no signi cant difference [17].…”
Section: Discussionmentioning
confidence: 92%